MANDALA MUSIC: DESCRIPTION INSTALLATION WORKSHOP (Journal de la Musique Omniprésente, 2026)
Mandala Music is a composition method for amateurs. Similar to sudoku, but in a larger area and according to rules that allow more freedom, the user enters numbers from 0 to 9 in a square matrix. Through continuous updates, the resulting number structure is transformed into a musical composition and provided to the user as feedback. The rules of Mandala Music require the user to create rhythmic patterns with the numbers, which should also be reused in parts if possible. In this respect, the rules force the user into musical thought patterns and challenge him to act creatively within these thought patterns